Study of the Properties of Cellulose Obtained from Amaranth Stem - Bokhodirovich , Karimov Bakhrom; Shukhratovna, Khasanova Makhfuza; Sodiqovich, Mukhamedyarov Kamildjan; Abdumalikovich, Abdumajidov Anvar (Researchparks Publishing, 2023)
There is an opportunity to extract cellulose from the wastes of medicinal and agricultural plants and use them as a good raw material for making paper, which is important for non-forestry countries. Within this study, the kinetics of the process of cellulose extraction from amaranth stem was studied, and the properties of the obtained cellulose were studied. Based on the conducted experiments, a technological mode of cellulose extraction from amaranth stems is proposed.